2005
DOI: 10.1007/s00467-004-1800-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative renal histomorphometry: a case study of oligonephropathy of prematurity

Abstract: Children born with very low birth weight have a decreased nephron number. Low nephron mass is associated with adult hypertension, proteinuria, and diabetes mellitus. The histomorphometry and radial glomerular count (RGC) of a total nephrectomy from a child with renal disease associated with extreme prematurity was compared with the kidney from a full-term age-matched child of normal gestation with chronic renal failure due to focal and segmental glomerulosclerosis (FSGS) and to a child without renal disease. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 10 publications
(37 reference statements)
2
57
0
1
Order By: Relevance
“…However, it has been consistently shown that intrauterine growth restriction leads to a reduced number of nephrons (5). There are data suggesting that premature birth (i.e., before completion of nephrogenesis) is also associated with a reduced nephron endowment (6,7). This may be due to extrauterine growth restriction, which is very common in premature infants (8) and which we have shown to lead to a reduced nephron number in an animal model (9).…”
Section: Renal Developmentmentioning
confidence: 70%
“…However, it has been consistently shown that intrauterine growth restriction leads to a reduced number of nephrons (5). There are data suggesting that premature birth (i.e., before completion of nephrogenesis) is also associated with a reduced nephron endowment (6,7). This may be due to extrauterine growth restriction, which is very common in premature infants (8) and which we have shown to lead to a reduced nephron number in an animal model (9).…”
Section: Renal Developmentmentioning
confidence: 70%
“…Evidence of long-term renal impairment has been found by Rodriguez-Soriano et al (46) with abnormal tubular phosphate transport along with urinary calcium excretion, however, they found no difference in blood pressure. Changes in renal histomorphometry have been noted in extremely premature infants (47,48), indicating that oligonephropathy can occur and may subsequently predispose these infants to renal disease and hypertension later in life. Our study, although not showing glomerulosclerosis, has indicated far more extensive glomerular injury than expected following exposure to these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Radial glomerular counts (RGCs) were determined on mid-longitudinal sections as mean glomerular generations from eight different 10ϫ photomicrograph fields of kidney cortex, with care to include the corticomedullary junction (20,21). Generations were identified by drawing parallel lines perpendicular to a mid-kidney medullary ray starting at the first glomerulus seen at the corticomedullary junction, continuing the process to the capsule, and ensuring every glomerulus traverses a line (20).…”
Section: Animalsmentioning
confidence: 99%